The Tip of the Iceberg: Cryopreservation Needs for Meeting the Challenge of Exceptional Plant Conservation - Valerie C. Pence; Emily Beckman Bruns (Plants, 2022)
Cryopreservation is increasingly important as a conservation tool, particularly for threatened exceptional species. The goal of this study was to investigate the current knowledge of plant cryopreservation through a search of the literature in Web of Science and align that with the 775 species currently identified on the Working List of Exceptional Plants. While there is a good foundation in plant cryopreservation research, particularly with economically important species, there are significant gaps in research on families that contain the largest numbers of currently known exceptional species, including the Dipterocarpaceae, Rhizophoraceae, and Pittosporaceae. Even families well represented in both in the literature and on the List of Exceptional Plants had much less overlap at the level of genus. Tropical trees, a significant portion of exceptional species, were not as well represented in the literature as herbaceous species. Over 70% of all articles dealt with in vitro cryopreservation, with much less emphasis on other methods (seed, embryo, dormant bud, and pollen) that will be more cost-effective for species where they can be applied. While the research on plant cryopreservation to date provides a strong foundation and is being utilized effectively for conserving the diversity of a number of economically important species, this study revealed significant gaps that can help prioritize future research to more effectively conserve the diversity of threatened exceptional species.